2011
DOI: 10.1074/mcp.m110.007138
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Spatial Protein Organization of the Postsynaptic Density Isolated from Porcine Cerebral Cortex and Cerebellum

Abstract: Postsynaptic density (PSD) is a protein supramolecule lying underneath the postsynaptic membrane of excitatory synapses and has been implicated to play important roles in synaptic structure and function in mammalian central nervous system. Here, PSDs were isolated from two distinct regions of porcine brain, cerebral cortex and cerebellum. SDS-PAGE and Western blotting analyses indicated that cerebral and cerebellar PSDs consisted of a similar set of proteins with noticeable differences in the abundance of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…Mass spectrometry studies indicate that actinins are components of the postsynaptic density (PSD) (56,57), underscoring their presence at postsynaptic sites. Consistent with biochemical findings, Actn2, for which ultrastructural information is available, has been shown to localize in apposition to the PSD and the spine apparatus within dendritic spines (58).…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry studies indicate that actinins are components of the postsynaptic density (PSD) (56,57), underscoring their presence at postsynaptic sites. Consistent with biochemical findings, Actn2, for which ultrastructural information is available, has been shown to localize in apposition to the PSD and the spine apparatus within dendritic spines (58).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, MAP2 is an important regulator of dendritic development and plasticity [2631]. As a core constituent of the post-synaptic density in spines [32], MAP2 also binds filamentous actin [33]. Because dendritic spine plasticity depends on actin and microtubule dynamics, it is thus not surprising that spine plasticity is also effected by MAP2 [34–38].…”
Section: Dendritic Alterations In Schizophreniamentioning
confidence: 99%
“…Moreover, anti-depressant therapy with citalopram reversed both the antineurogenic and the behavioral impacts of persistent stress following brain ischemia [8]. Recently, it was reported that the cerebellum may exhibit a role in psychiatric illness, behavior and cognition [9, 10]. Cerebellum dysfunction might be involved in pathogenesis of PSD, based on the correlation between the cerebellum and the affective disorder, similarity in pathology between PSD and neuropsychiatric diseases (particularly for depression), and the clinical trial indicating that cerebella substantially relives symptom of PSD upon activation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the cerebellum may exhibit a role in psychiatric illness, behavior and cognition [9, 10]. Cerebellum dysfunction might be involved in pathogenesis of PSD, based on the correlation between the cerebellum and the affective disorder, similarity in pathology between PSD and neuropsychiatric diseases (particularly for depression), and the clinical trial indicating that cerebella substantially relives symptom of PSD upon activation [10]. But there is little evidence that investigates the putative cerebellar effect in PSD [11].…”
Section: Introductionmentioning
confidence: 99%